Ethics in Early China : an Anthology - Fraser, Chris; Robins, Dan; O'Leary, Timothy (Hong Kong University Press, 2011)
Early Chinese ethics has attracted increasing scholarly and social attention in recent years, as the virtue ethics movement in Western philosophy sparked renewed interest in Confucianism and Daoism. Meanwhile, intellectuals and social commentators throughout greater China have looked to the Chinese ethical tradition for resources to evaluate the role of traditional cultural values in the contemporary world. Publications on early Chinese ethics have tended to focus uncritical attention toward Confucianism, while neglecting Daoism, Mohism, and shared features of Chinese moral psychology. This bo.